2017
DOI: 10.1044/2016_jslhr-l-15-0417
|View full text |Cite
|
Sign up to set email alerts
|

Late Talkers: A Population-Based Study of Risk Factors and School Readiness Consequences

Abstract: Limited vocabulary knowledge at 24 and 48 months is uniquely predictive of later school readiness. Young children with low vocabularies require additional supports prior to school entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 105 publications
4
59
1
5
Order By: Relevance
“…Variance in expressive vocabulary size has been attributed to heritability, child gender, birth order, caregiver speech rate and quality, temperament, and attentional factors (Hammer et al, 2017;Rowe & Leech, 2017). Some studies into variance in expressive vocabulary size have also focussed on identifying the lexical characteristics that make a particular word easy or difficult for certain children to learn and produce.…”
mentioning
confidence: 99%
“…Variance in expressive vocabulary size has been attributed to heritability, child gender, birth order, caregiver speech rate and quality, temperament, and attentional factors (Hammer et al, 2017;Rowe & Leech, 2017). Some studies into variance in expressive vocabulary size have also focussed on identifying the lexical characteristics that make a particular word easy or difficult for certain children to learn and produce.…”
mentioning
confidence: 99%
“…Most studies have focused exclusively on age groups up to preschool age (e.g., Fernald & Marchman, ; Girolametto, Wiigs, Smyth, Weitzman, & Pearce, ; Marschik, Einspieler, Garzarolli, & Prechtl, ; Moyle, Weismer, Evans, & Lindstrom, ; Rescorla, Dahlsgaard, & Roberts, ; Rescorla & Turner, ; Sachse & von Suchodoletz, ; Thal, Miller, Carlson, & Vega, ). Language outcomes at ages 4 and 5 indicate that – in small sample sizes, in which LTs are thoroughly diagnosed and well selected – a large proportion of LTs scored within the normal range (see Rescorla, ); a result which was supported by epidemiological studies at age 4 (Dale, Price, Bishop, & Plomin, ; Hammer et al, ; Reilly et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Other studies that report school‐age outcomes including reading and spelling assessments found relationships between early language assessments (as expressive vocabulary size) and reading outcomes prior to school enrolment (Hammer et al, , large‐scale), at early adolescence in TDC (Bartl‐Pokorny et al, ) and in population‐based studies (Bleses, Makransky, Dale, Hojen, & Ari, ; Lee, ).…”
Section: Introductionmentioning
confidence: 97%
“…Il est entendu dans la littérature scientifique que le développement de la compétence à lire est déterminant pour la réussite et la persévérance scolaires des élèves tout comme l'est la qualité de l'enseignement qu'ils en reçoivent (Hammer et al, 2017;Hattie, 2009 Roberts et Meiring, 2006;Spear-Swerling et Cheesman, 2012). Cette compétence repose entre autres sur la compréhension de lecture qui implique que l'élève comprenne le sens du message véhiculé grâce à des habiletés langagières réceptives alliant le vocabulaire, la morphosyntaxe et les inférences (Nation, Clarke, Marshall et Durand, 2004;Oakhill et Cain, 2004).…”
Section: Introductionunclassified